Act East Policy: Analisis Faktor Internal dan Eksternal India dalam mengeluarkan Act East Policy terhadap Korea Selatan (2014-2019) - Ni Putu Dyana Prabhandhari; Maria Indira Aryani (Andalas Institute of International Studies, 2021)
The Asian region is undergoing significant changes, along with the rise of China as a new power since Deng Xiaoping's leadership. The increasing power of China has caused unrest not only for countries in the Asian region, but also for other Western countries, such as the United States. Increasing China's power has the potential to destabilize the region. One of the countries experiencing unrest with the disruption of regional stability due to China's increasing power is India. In order to keep India from being affected by the regional instability, India is promoting improved relations with its neighboring countries and identifying potential non-traditional partners by issuing the Act East Policy. With Act East Policy, India seeks to improve relations with one of its potential trading partners, namely South Korea. This research is then aimed at analyzing the factors that led India to choose South Korea as the target of the Act East Policy from 2014 to 2019. This research will be analyzed using a qualitative explanative method and using a determinant thinking base of foreign policy and strategic environment. Based on the author's analysis, the factors that underlie India choosing South Korea can be divided into internal factors, namely the change of leaders in India and Indian economic conditions, and external factors, namely bilateral relations between the two countries.